THE DYNAMICS OF THE GRIEVING PROCESS AMONG ADOLESCENTS WHO HAVE LOST A PARENT, BASED ON THE KUBLER-ROSS THEORY - Aprila Wulandari; Andi Wahyu Irawan (LP2M IAI Al-Khairat Pamekasan, 2026)
The death of a parent is an event that has a deep traumatic impact on a child, especially in emotional and psychological aspects. This grieving experience is a complex and different process for each individual, especially when experienced at the adolescent development stage which is full of personal changes. This research aims to explore the dynamics of the grieving process in adolescents who experience the loss of a parent based on Kubler Ross's theory. The method used is a qualitative method with a case study approach. The data collection process was carried out through observation, semi-structured interviews, documentation in the form of voice recordings and photo elicitation which lasted for three months until data saturation was reached. The selection of participants was carried out using purposive sampling with the criteria of female teenagers who had experience of losing their parents, and were willing to become respondents. The respondents consisted of 3 participants. The data analysis technique goes through four stages, namely data collection, data reduction, data presentation, and drawing conclusions. The research results showed that all participants experienced emotional and psychological responses when going through Kubler Ross's five stages of grief, namely denial, anger, bargaining, depression and acceptance. The grief process experienced by participants is complex, does not run linearly, and is influenced by various personal and contextual factors. Acceptance is not a final, final stage, but rather an ongoing process that continues to transform according to the individual's psychological condition, the social support received, and the way the teenager interprets the loss.